Lithium rechallenge after renal transplant - Beasley, Anna K. (Ment Health Clin, 2018)
Mrs B is a 65-year-old, married, white woman with long-standing history of bipolar disorder type I who achieved mood stability with chronic lithium treatment. She developed end-stage renal disease, which was suspected to be the result of chronic lithium exposure in the context of medical comorbidity, and subsequently required renal transplantation. Following transplantation and discontinuation of lithium, Mrs B was unable to achieve mood stability with multiple medication trials and required more than 40 medical and psychiatric hospitalizations with eventual transition to skilled nursing care. After much discussion among the psychiatric treatment team, the patient, and her husband, primary care provider, nephrologist, and renal transplant surgeon, the decision was made to restart the patient on lithium given her previous treatment success. The purpose of this case report is to discuss the use of lithium following renal transplantation. In this case, a multidisciplinary approach was used to assist the patient in carefully weighing the risks and benefits of her treatment decisions. The consensus of the patient, her husband, and her providers was that the benefit of mood stabilization outweighed the potential risks of renal toxicity. Although treatment with lithium after renal transplant is not a first-line treatment option, this case illustrates that lithium could be considered in certain cases.